Gambaran Tingkat Kecukupan Energi dan Tingkat Kecukupan Protein Ibu Hamil di Kota Malang - Ekawati, Rany; Rahmawati, Windi Chusniah; Paramita, Farah; Berliana, Dini Elita; Fariadi, Alfinadelasari Putri (Preventia: The Indonesian Journal of Public Health, 2022)
Chronic energy deficiency (CED) in pregnant women is still a nutritional problem in Indonesia. CED in pregnant women is caused by low energy and protein intake in pregnant women. The low energy and protein intake in pregnant women can cause disturbances in pregnancy and the baby in the womb. This research objective is to provide an overview of the level of energy and protein adequacy of pregnant women in the city of Malang. This study is a quantitative study with a cross-sectional design. The sample in this study was 64 pregnant women. The variables of energy adequacy and protein adequacy were obtained through online interviews. The instrument in this study used a Semi-Quantitative Food Frequency Questionnaire. Data analysis is descriptive. The results showed that the energy adequacy level was categorized as very less (54.7 percent), less (28.1 percent), normal (10.9 percent), and more (6.3 percent). The level of protein adequacy is categorized as very less (45.3 percent), less (23.4 percent), normal (7.8 percent), and more (23.4 percent). The level of energy and protein adequacy in pregnant women is at most included in the minimal category or very less compared to needs. Efforts to accelerate the fulfillment of energy and protein in pregnant women.